Effect of the Size and Concentration of Pp-G-Mah on The Physical and Mechanical Properties of Compound Materials - Abdukarimova S. A.; Yodgorov N. N.; Makhkamova L. K.; Atakuziyeva D. A. (Scholars Digest Publishing, 2023)
Polyolefins are cheap products and are among the most commonly used synthetic polymers and have valuable consumer properties. Since polyolefins have high thermal stability, they replace metals in the field of household appliances and mechanical engineering, namely in individual parts of the car structure. Since the physico-chemical properties of polyolefins are insufficient for the application in the area we need, we resort to modification by compounding them with various fillers to improve their quality.
Keywords: fiber, compatibilizer, polymer, glass, basalt.